Thromboelastography as a predictor of functional outcome in acute ischemic stroke patients undergoing endovascular treatment. Issue 225 (May 2023) - Ryu, Jae-Chan; Jung, Seunguk; Bae, Jae-Han; Ha, Sang Hee; Kim, Bum Joon; Jeon, Sang-Beom; Kang, Dong-Wha; Kwon, Sun U.; Kim, Jong S.; Chang, Jun Young
Abstract: Background: Thromboelastography (TEG) is a useful for predicting hemorrhagic transformation, early neurological deterioration, and functional outcome after stroke. We aimed to investigate whether TEG value could also be useful in predicting functional outcome via various intraprocedural and postprocedural factors in patients with acute large vessel occlusive stroke who underwent intraarterial thrombectomy (IAT). Methods: Patients with ischemic stroke who underwent IAT between March 2018 and March 2020 at two tertiary hospitals were included. The association between reaction time (R) and functional outcome was evaluated. The primary outcome was the achievement of functional independence defined as the achievement of a modified Rankin Scale (mRS) score of 0–2 at 3 months after the index stroke. Results: Among a total of 160 patients (mean age, 70.6 ± 12.3 years; 103 [64.4 %] men), 79 (49.3 %) achieved functional independence at 3 months. R, both as a continuous (odds ratio [OR]: 1.45, 95 % confidence interval [95 % CI]: 1.09–1.92, P  = 0.011) and dichotomized parameters ( R  < 5 min [OR: 0.37, 95 % CI: 0.16–0.82, P  = 0.014]), were inversely associated with increased odds of achieving functional independence (mRS score 0–2) after multivariable analysis. The association was still consistent when the outcome was the achievement of disability free (mRS score 0–1) or mRS score analyzed as an ordinal variable. Conclusions: Decreased R, especially R  < 5 min, was inversely associated with functional outcome pf stroke after EVT. Highlights: Thromboelastography (TEG) could provide the coagulation and fibrinolysis pathways. We present a study of stroke outcomes after thrombectomy according to the reaction time (R). Decreased R, especially R  < 5 min, was inversely associated with stroke outcome after thrombectomy. R can be a useful TEG parameter for predicting functional independence after thrombectomy.